The Effectiveness of use of Hold Finger and Hypnobirthing Techniques in Reducing Pain Levels in Women in the First Stage of Labor - Nindia Aristiya; Faizah Betty Rahayuningsih (Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
Childbirth is a physiological process experienced by all pregnant women and is a process that mothers are waiting for to meet the baby they are carrying. All labor causes pain. One of the causes of labor pain is contractions. Excessive pain can also be caused by the mother's psychology, such as excessive anxiety and fear. Therefore, there is a need for non-pharmacological interventions such as the hold finger and hypnobirthing technique to help reduce the level of pain in mothers in the 1st stage of labor. The aim of writing this article is to determine the effectiveness of providing finger hold techniques and hypnobirthing interventions in reducing the level of pain in mothers in the 1st stage of labor. This type of research is quantitative using a case study approach method by implementing finger grasping techniques and hypnobrithing interventions for mothers in the 1st stage of labor. The sample of this study consisted of 6 mothers in labor. The instrument used in this research is the Numeric Rating Scale. Based on the results of data analysis using the Wilcoxon test, the p value = 0.020 (p value < 0.05) meaning that the hypothesis is accepted, namely that there is a significant influence between the use of the finger grip technique and hypnobirthing with a decrease in the intensity of pain in mothers in the 1st stage of labor. From these results it can be concluded that the use of finger holding techniques and hypnobirthing are effective for mothers in the 1st stage of labor to help reduce pain levels.